2016
DOI: 10.5433/1679-0359.2016v37n6p3847
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Forest soil as reference in the soil quality evaluation of coconut orchards (Cocos nucífera L) under different management

Abstract: The evaluation of the soil quality is important to identify potential problems of soil degradation. The assessment of the soil quality requires the determination of several soil parameters and the integration of specific soil properties measurements into mathematical models, such as the soil quality index (SQI).The aims of this study were to: (i) determine the SQI for an Ultisol under a remnant of Atlantic rain forest; (ii) use the SQI for the Atlantic rain forest as a reference to evaluate the effects of conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Corrêa et al (2009) reported soil organic matter content lower than 1% in irrigated perimeters of Pernambuco state. Gonzaga et al (2016) also reported low organic matter content (1.1%) in Ultisols under irrigated coconut orchards in the state of Sergipe.…”
Section: Soil Chemical Attributesmentioning
confidence: 84%
“…Corrêa et al (2009) reported soil organic matter content lower than 1% in irrigated perimeters of Pernambuco state. Gonzaga et al (2016) also reported low organic matter content (1.1%) in Ultisols under irrigated coconut orchards in the state of Sergipe.…”
Section: Soil Chemical Attributesmentioning
confidence: 84%
“…An alternative would have been to use forest as a reference system, which could possibly have indicated that both organic and IPM agricultural systems are, in fact, not reaching full soil health potential. This was for instance the case in Gonzaga et al (2016) and Ortiz et al (2017), where soils under perennial sugarcane crops and coconut orchards in Brazil were found to be of less quality compared to soils under native Atlantic forest.…”
Section: Comparison With a Semi-natural Reference Systemmentioning
confidence: 95%
“…Soil is the basis for the survival of humans, animals, and plants [ 1 ], as well as the living space for numerous microorganisms [ 2 ]. Soil quality is the comprehensive expression of soil’s physical, chemical, biological, and other properties.…”
Section: Introductionmentioning
confidence: 99%